How Competency Shapes Employee Performance Through Motivation - Kustono, Hendra; Suyono, Joko; Utomo , Agung Budi Widi; Harindrayana, Harindrayana; Elisabeth, Damarsari Ratnasahara (INNOVATION RESEARCH JOURNAL, 2025)
This research was conducted at the Surabaya City Public Housing, Settlement Areas, and Land Agency. The aim was to analyze the influence of competency on employee performance, with motivation as a mediating variable. The population in this study was 75 employees of the Surabaya City Public Housing, Settlement Areas, and Land Agency, Surabaya, East Java, Indonesia. The sampling technique used total sampling. Data analysis used Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results showed that competency influences employee performance and motivation, motivation influences employee performance, and competency influences employee performance through motivation.